Elizabethkingia meningoseptica Infection in a Neonate: Case Report - Davis, Sandhra; Biju, Roshni Acha; Sanal, Ganga (Journal of Pharmacy Practice and Community Medicine)
Elizabethkingia meningoseptica is a gram-negative bacteria associated with multiple nosocomial infections normally present in hospital environments. In particular, preterm neonates are more susceptible to develop serious infections. This is a case of E. meningoseptica septicemia that was detected early in an extremely premature low birth weight infant with other co morbidities, He was successfully treated with a combination of levofloxacin and Meropenem. The spread of infection was controlled with no other reported cases. Accurate and early detection with appropriate sensitivity testing is mandatory to reduce morbidity in patients with E. meningoseptica.
Keywords: Elizabethkingia meningoseptica; Nosocomial infections; Preterm infant; Active surveillance.